Climate justice and disaster law - Lyster, Rosemary (Cambridge, 2015)
"Climate disasters demand an integration of multilateral negotiations on climate change, disaster risk reduction, sustainable development, human rights and human security. Via detailed examination of recent law and policy initiatives from around the world, and making use of a capability approach, Rosemary Lyster develops a unique approach to human and non-human climate justice and its application to all stages of a disaster: prevention; response, recovery and rebuilding; and compensation and risk transfer. She comprehensively analyses the complexities of climate science and their interfaces with the law- and policy-making processes, and also provides an in-depth analysis of multilateral climate change negotiations dating from the establishment of the 1992 United Nations Framework Convention on Climate Change (UNFCCC) to the Twentieth Conference of the Parties in Lima (COP 20) in December 2014"--